Inordinately strange life of Dyce Sombre : victorian anglo-indian M. P. and Chancery Lunatic - Fisher, Michael H. (New Delhi, 2010)
The descendant of German and French Catholic mercenaries, a Scots Presbyterian subaltern, and their secluded Indian wives, David Ochterlony Dyce Sombre defied all classification in the North Indian principality where he was raised. Add to these influences an adoptive mother who began as a Muslim courtesan and rose to become the Catholic ruler of a strategically-placed, cosmopolitan little kingdom, which her foster son was destined to inherit, and you have the origins of a fascinating life that reflects many of the Romantic, political, and colonial trends of a century. As heir to the throne, Sombre took great advantage of the sensuous pleasures of privilege, but he lost his kingdom to the British and went into exile in London with his very considerable fortune. Despite being Indian and Catholic, Sombre married the daughter of an English Protestant Viscount, who was a prominent defender of slavery. Sombre bought himself election as a British MP but then was expelled for corruption. His treatment of his aristocratic wife led to his arrest and confinement as a Chancery lunatic. Fleeing to France, Sombre spent years trying to reclaim his sanity and his fortune from those among the British establishment who had done him down. In this thrilling biography, Michael H. Fisher recovers Sombre's strange story and the echoes of his case for modern conceptions of race, privilege and empire.
Keywords: Legislators